Perancangan Customer Knowledge Management pada PT Pandawa Maju Perkasa - Joni Suhartono; Caleb Kosashi (Bina Nusantara University, 2014)
In the era of global trade, more countries want a quality of product with optimal price. PT Pandawa Maju Perkasa engaged in export trade services requires an application that can bridge the communication between the customer and the company. It can also create appropriate knowledge to present the product to the customer. Knowledge of the product obtained will be shared to the customer as company's marketing activities. In addition, critics and suggestions are very necessary for the improvement of customer service of the company. Research in this study was done by analyzing business process, designing model of knowledge management system, and designing system model. The design of the system made consisted of making class diagrams, use case diagrams, sequence diagrams, and user interface. The design of the CKM system will help the company capture customer demand for the goods they want, the communication between the customer and the company can be well established, critics and suggestions facility made is used to improve services to customers.